Qualificação e atribuições do profissional da informação em sistemas de documentação e informação em ciência e tecnologia - Faria, Clarice Muhlethaler de Souza (1983)
A survey of information professional profile in scientific and technological information and documentation systems, identifying and describing professional qualifications and functional attributes in order to analyse existent association between educators intensity level of subject approach and the information professional intensity level of functional attributes performance. Opinions were collected by structured questionnaires applied to Documentation and Information Science educators population of Rio de Janeiro State and information professional population in scientific and technological documentation and information systems of Rio de Janeiro city during period of 27.10.81 to 10.12.82. The association hypothesis was tested on level of significance of 0,05 by the x2 (chi square) test. The frequency and the association x2 (chi square) test were realized by SPSS – Statistical Package for Social Science – version 7 (1975). The survey results point out the existent independence between educators intensity level of subject approach and the information professional performance level of functional attributes in scientific and technological documentation and information systems.